2021
DOI: 10.1186/s12903-021-01745-3
|View full text |Cite
|
Sign up to set email alerts
|

Composite surface roughness and color change following airflow usage

Abstract: Background Esthetic dental restorations have gained increasing popularity. The surface of restorations should be smooth enough to achieve maximum esthetics and prevent the adhesion of microorganisms and food particles. This study aimed to assess the surface roughness and color change of composite specimens following airflow usage. Methods In this in vitro, experimental study, 30 Tokuyama composite discs were fabricated and randomly divided into thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A recent study evaluated that FDM process induces a reduction in surface layer hardness compared to injection-molded PEEK, which could lead to a decrease in the wear resistance of the material [ 32 ]. Gao et al evaluated that the surface roughness of the polished FDM 3D-printed PEEK samples was close to that of amalgam and some ceramic or composite materials used in dental applications [ 32 , 44 , 45 ]. There is a need to evaluate these properties in clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluated that FDM process induces a reduction in surface layer hardness compared to injection-molded PEEK, which could lead to a decrease in the wear resistance of the material [ 32 ]. Gao et al evaluated that the surface roughness of the polished FDM 3D-printed PEEK samples was close to that of amalgam and some ceramic or composite materials used in dental applications [ 32 , 44 , 45 ]. There is a need to evaluate these properties in clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that air polishing should be avoided on all types of RBCs [17]. The mean value of RA as a result of a prophylactic air-polishing can range between 0.3 and 10 µm, and depends on the type of applied powder, exposure time, pressure, and the type of the recipient RBC [17][18][19][20]. However, according to our best knowledge, there is no report in the literature about the effect of sodium bicarbonate air-polishing on the microtensile bond strength (µTBS).…”
Section: Introductionmentioning
confidence: 99%
“…There are studies about the efficiency of the APPs in removing discolorations and the staining susceptibility of restorative materials that are exposed to air-polishing and staining solutions afterward [31][32][33]. However, to the best of the authors' knowledge, there is no research on how these APPs themselves affect the color stability of indirect restorative materials such as resin matrix ceramics.…”
Section: Introductionmentioning
confidence: 99%